1999
DOI: 10.1002/(sici)1097-0207(19990730)45:9<1277::aid-nme630>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

On the eigenvalues of a uniform cantilever beam carrying any number of spring-damper-mass systems

Abstract: SUMMARYThe eigenvalues of a uniform cantilever beam carrying any number of spring}damper}mass systems with arbitrary magnitudes and locations were determined by means of the analytical-and-numerical-combined method (ANCM). First of all, each spring}damper}mass system was replaced by a massless e!ective spring with spring constant k , which is the main point that the ANCM is available for the present problem. Next, the equation of motion for the &constrained' beam (with spring}damper}mass systems attached) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Other approaches to evaluate mode damping based on the principle of virtual work have also been applied (Chen et al 2009, Jeremiah 2006. Further relevant studies using the continuous cantilever model can be found in beam vibration control theory from the applied mechanics field (Wu et al 1998(Wu et al , 1999Laura et al 1977). These methods require validation against a range of building heights and further simplification to be of practical use.…”
Section: Introductionmentioning
confidence: 99%
“…Other approaches to evaluate mode damping based on the principle of virtual work have also been applied (Chen et al 2009, Jeremiah 2006. Further relevant studies using the continuous cantilever model can be found in beam vibration control theory from the applied mechanics field (Wu et al 1998(Wu et al , 1999Laura et al 1977). These methods require validation against a range of building heights and further simplification to be of practical use.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, Gürgöze (1998) studied the sensitivities of the eigenvalues of a cantilever beam with a viscous damper in span and a tip mass at the free end. Wu et al. (1999) investigated the eigenvalues of a cantilever beam with arbitrarily attached dampers by using the analytical-and-numerical-combined method (ANCM).…”
Section: Introductionmentioning
confidence: 99%
“…It is found that the damper attached to a cable or beam can effectively increase the damping ratio and thus suppress the vibration. There are also some publications investigating the free vibration of a beam carrying spring-damper-mass systems [19][20][21], and some spring-damper-mass systems are designed to behave as vibration absorbers to mitigate the vibrations of a beam [22,23]. However, to the best of the authors' knowledge, the free vibration of a beam-tendon system interconnected by intermediate spring-damper elements and in a rotating configuration has not been studied so far.…”
mentioning
confidence: 99%